Níveis de proteína e aminoácidos em dietas para frangos de corte fêmeas abatidos em diferentes idades - Anna Rosa Chagas Abreu (2019)
A total of 390 broiler chickens were used at 21 days of age to evaluate the effect of five protein manipulations on the diet (19P - 19% protein, 21P - 21% protein, 19E - 19% protein, 21E - 21% protein ; 19E + Aa - 19% protein) and two slaughter ages (38 and 46 days). Nutrient metabolizability, performance, carcass yield, myopathies, blood biochemical profile and production costs were evaluated. The design was completely randomized (DIC) with five treatments (diets) and six replicates for metabolizability; DIC in a factorial scheme (5 rations x 2 ages) for performance, carcass yield, myopathies and production costs; and DIC in subdivided plots for blood biochemical profile. Lower metabolizable dry matter was found in the 21E treatment (p≤0.05). The 19E + Aa treatment improved protein utilization and reduced nitrogen excretion (p≤0.05). The treatments 19E, 21E and 19E + Aa improved the metabolizable of ethereal extract (p≤0.05). Lower value of metabolizable energy was observed in the 21P diet (p≤0.05). There was no interaction between feed and age for any of the variables (p> 0.05). Diet 19P increased feed intake (p≤0.05); in addition, higher feed intake and weight gain were observed at 44 days than at 37 days (p≤0.05). The 19P diet worsened the feed conversion and the productive efficiency index (p≤0.05). The 19P and 21P diets had better production costs (p≤0.05). There was no effect of diets on carcass yield, breast, thigh + overcooked (p> 0.05). However, carcass and chest yields were higher for broilers slaughtered at 46 days than at 38 days (p≤0.05). There was no effect of diets or ages on the white strping score (p> 0.05) or the woody breast (p> 0.05). There was no effect of the diets on the blood biochemical profile and enzymes (p> 0.05). At 37 days LDL - cholesterol levels (p≤0.05) and total proteins (p≤0.05) were higher than at 25 days. At 37 days, lipase levels (p≤0.05) were lower than at 25 days. It is concluded that the protein manipulation of the diet 21P may be more for performance and costs for female broiler chickens from 21 to 37 days, and from 21 to 44 days. Slaughter of 46-day-old broilers increase in carcass and breast yield without altering the incidence of macroscopic myopathic lesions when compared to slaughter at 38 days. In addition, diets and ages did not cause significant changes in the blood biochemical profile and enzymes of female broilers.